Common menstrual complaints and use of medication, among undergraduate students of Moradabad, Uttar Pradesh, India: a cross sectional study - Shukla, Mahesh Kumar; Khan, Samreen; Srivastava, Anurag (International Journal Of Community Medicine And Public Health, 2017)
Background: Menses is associated with many complaints in girls. Very little work is done on prevalence of menstrual problems among Indian population. Problem of pain is by far the most common problem reported by majority of girls. This has an impact on public and occupational health. In India the girls hesitate to discuss these problems even with their parents. Thus most of the time either they do not take any medication to resolve their problem, or take some pills on their own to get relief. Finding out the common menstrual problems and the pattern of medication use will be helpful in planning a health care program for the population. Objectives of the study were to assess the prevalence of common menstrual complaints among under-graduate students of Moradabad region and to assess the pattern of medication, used by them, for these complaints. Methods: 396 female first year students pursuing undergraduate course were studied with the help of a structured pilot tested questionnaire. Results: 93.4% girls were found to have some or the other complaint during menstruation. Body-ache (64%) was the most common complaint reported followed by pain in abdomen (59%) and backache (57%). 37.9% subjects reported to use some medicine for menstrual problems. 65.3% of those who used medicine used it for pain in abdomen, either alone or in combination with some other complaints. Only 23.9% of those belonging to rural background consulted doctor before using medicine, as against 48.3% of those belonging to urban background. Conclusions: Present study shows a high prevalence of medical problems during menstruation. Mostly medicines were used for the pain in abdomen either alone or in combination with other complaints. Menstrual problems constitute an important unmet area of reproductive health services. Packages of reproductive health care should include modules for education, diagnosis and treatment of most menstrual morbidities.